Green Perceived Value Analysis of Green Repurchase Intention: The Role of Green Trust in Fast Moving Consumer Goods (FMCG) Products - Gibson Manalu; Nadia Ismi Avissa; Nelvika Darlia; Binsar Sihombing (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The increasing number of news reports in the mass media about global warming and environmental damage has now become a neglected issue. This has triggered customers to value environmentally friendly products more. The focus of this study is to analyze how perceived green values are related to the intention to repurchase green cosmetic products by using green beliefs as an intervening variable. This study used purposive sampling to collect a sample of 96 respondents. This study used the path analysis method. The results of the analysis indicate that perceived green values have a positive and significant effect on green purchase intentions; perceived green values have a positive and significant effect on green purchase intentions; perceived green values have a positive and significant effect on green purchase intentions; and perceived green values significantly mediate the effect of perceived green values on green purchase intentions. In the future, it is hoped that cosmetic companies will promote the benefits of using green cosmetic products more, as well as improve the quality and quality of the products they produce.